Utilization of Biomass Waste from Banana (Musa Paradisiaca) and Breadfruit (Artocarpus Communis) Peel for Development of Bio-Batteries - Salawali, Rismul Trianto; Lestari, Sri Ayu; Nurhajawarsi; Yusriadi (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
Bio-batteries are one alternative as well as a solution to the limited use of electrical energy. Batteries that are widely used today are sourced from chemicals in the form of heavy metals such as mercury, lead, cadmium, and nickel, which can pollute the environment if not disposed of properly. Efforts to reduce the use of chemicals that pollute the environment need innovation to overcome the problem. This study aims to determine the formula for bio-batteries that have a long life. The method used is to mix banana peel and breadfruit peel that has been fermented with variations of b/vv (g/mmL) with a composition of 0, 25, 50, 75, and 100% at each concentration. The parameters observed in this study were pH and voltage measurements during the fermentation process for 7 days, and the bio-batteries that had been made were tested for potential differences in electric current, power, resistance, and durability. As a result, the optimum condition of the bio-battery was obtained in a mixture of 75% banana peel compared to 25% breadfruit peel by producing a potential difference of 1.37 V, an electric current of 1.5 mA, and a power of 0.68 mW. A bio-battery with a composition of 75% banana peel compared to 25% breadfruit peel can last a maximum of 31 hours and 28 minutes when used on a wall clock.